Natural hydroxyapatite synthesis from fish bones: "Atlantic Bonito" (Sarda sarda) - (:unkn) unknown (Trans Tech Publications Ltd, 2017)
Hydroxyapatite (HA) is produced from animal sources like bovine-sheep bones and from human sources with different techniques. Nowadays, it is very crucial utilizing higher valued products from waste materials. Especially, fish bones become major sources for HA production. We have used the waste bone of "Atlantic Bonito" (Sarda sarda), which is a very characteristic fish species. It lives through Atlantic Ocean, the Mediterranean Sea and up to the Black Sea, where it is regarded as a point commercial fish. In this study, the fish bones of "Atlantic Bonito" (Sarda sarda) were collected and cleaned from flesh and greasy parts with distilled boiling water. It was washed again with distilled water, dried and calcinated for 4 hours at 850°C. Afterwards the material was analysed by X-ray diffraction (XRD) and scanning electron microscope (SEM). XRD analysis revealed the obtained bioceramic material is made of 66.7% HA and 33.3% TCP. The fish bone of "Atlantic Bonito" (Sarda sarda) can be easily trandformed to bioceramic material and it can be used in applications where partly resorbable and economic biomaterials with low carbon footprint needed. © 2017 Trans Tech Publications.
Keywords: Calcination; Fish bones; Hydroxyapatite; Sustainable natural sources; Tricalcium phosphate